Jeruk Ikan Masin Moyang-moyang / Fatin Sabrina Norazian...[et al.] - Norazian, Fatin Sabrina; Kamil, Siti Zhulaika; Abdul Rahim, Abdul Rahman; Jalaludin, Muhamad Afiq (2019)
We have been assigned to do an assignment of new product development. We choose "Jeruk Ikan Masin" as our new product. This "Jeruk Ikan Masin" has never been invented yet. Our business skills will focus on its research and development (RnD) that will come out with a new product. The concept of our product is "tasty and long lasting". The concept that our team want to bring to the world is "Eat Malaysia's Traditional Food".